A Cost-utility Analysis of Percutaneous Endoscopic Lumbar Discectomy for L5-S1 Lumbar Disc Herniation: Transforaminal versus Interlaminar. Issue 8 (15th April 2019) - Wang, Dongdong; Xie, Wangcheng; Cao, Wenxin; He, Shisheng; Fan, Guoxin; Zhang, Hailong
Abstract : Study Design: A cost-utility analysis (CUA). Objective: The aim of this study was to evaluate the cost-effectiveness of percutaneous endoscopic transforaminal discectomy (PETD) and percutaneous endoscopic interlaminar discectomy (PEID) techniques for the treatment of L5-S1 lumbar disc herniation (LDH). Summary of Background Data: The annual cost of treatment for lumbar disc herniation is staggering. As the two major approaches of percutaneous endoscopic lumbar discectomy (PELD): percutaneous endoscopic transforaminal discectomy (PETD) and percutaneous endoscopic interlaminar discectomy (PEID) have gained recognition for the treatment of L5-S1 lumbar disc herniation (LDH) and showed similar clinical outcome. ost-utility analysis (CUA) can help clinicians make appropriate decisions about optimal health care for L5-S1 LDH. Methods: Fifty and 25 patients were included in the PETD and PEID groups of the study. Patients' basic characteristics, health care costs, and clinical outcome of PETD and PEID group were collected and analyzed. Quality-adjusted life-years (QALYs) were calculated and validated by EuroQol five-dimensional (EQ-5D) questionnaire. Cost-effectiveness was determined by the incremental cost per QALY gained. Results: The mean total cost of the PETD group was $5275.58 ± 292.98 and the PEID group was $5494.45 ± 749.24. No significant differences were observed in hospitalization expenses, laboratory and radiographic evaluations expenses, surgical expenses, and drug costs. Surgical equipment and materials costs, and anesthesia expense in the PEID group were significantly higher than in the PETD group ( P  < 0.001). Clinical outcomes, including Oswestry Disability Index (ODI), Visual Analogue Scale (VAS) scores, and Japanese Orthopaedic Association (JOA), also showed no significant differences between the two groups. The cost-effectiveness ratio of PETD and PEID were $6816.05 ± 717.90/QALY and $7073.30 ± 1081.44/QALY, respectively. The incremental cost-effectiveness ratios (ICERs) of PEID over PETD was $21887.00/QALY. Conclusion: Observed costs per QALY gained for L5-S1 LDH with PETD or PEID were similar for patients, demonstrating that the two different approaches of PELD are equally cost-effective and valuable interventions. Level of Evidence: 5 Abstract : We conducted a cost-utility analysis(CUA) to evaluate the cost-effectiveness of PETD and PEID techniques for the treatment of L5-S1LDH. Observed costs per QALY gained for L5-S1 LDH patients with PETD or PEID were similar, demonstrating that the two different approaches of PELD are equally cost-effective and valuable interventions.